OPPORTUNITIES OF USING A COMPUTER IN OPTICS LABORATORIES - Abdulayeva Ә.Б.; Sakibayeva Б.Р.; Zhakpayev Қ.Р.; Zhanatbekova Н.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
Studies in the field of natural science education and the development of modern technology show that the principles of digitization of analog signals, sensors of physical quantities, computer processing of information obtained from such sensors are increasingly used in the measurement of physical quantities. The modern standard of higher education requires active mastering of modern methods of obtaining, processing and presenting information, as well as methods of conducting research work in physics. Thus, today the issue of introducing computer technologies in conducting laboratory and research works of students is relevant. The purpose of this study is the application of computer programs in the laboratory work «Determination of the radius of curvature of the lens with the help of Newton’s rings». The results of the conducted research have shown that the use of computer helps to increase the interest of students in the study of physical processes and raises the level of their conscious understanding.